Artificial intelligence in technique analysis - Past, present and future - Bartlett, R. (International Journal of Performance Analysis in Sport, 2004)
This paper reviews developments in the use of Artificial Intelligence in technique analysis over about the last ten years. I outline the potential uses of Expert Systems as diagnostic tools for evaluating technique 'errors' and present some example knowledge rules for such an expert system. I then compare technique analysis, in which Expert Systems appear to have found no place to date, with gait analysis, in which they are routinely used. Consideration is then given to technique analysis using Artificial Neural Networks, focusing on Kohonen self-organizing maps, which have been most widely used in technique analysis, and multi-layer networks, which have been far more widely used in biomechanics in general. Examples of the use of Kohonen maps in technique analysis are presented in javelin and discus throwing and in football kicking. Shot putting is the sole technique analysis presented using multi-layer networks. An example is given of the use of Evolutionary Computation in technique optimization, rather than technique analysis, in the soccer throw in, which predicted an optimal technique close to that in the coaching literature. I conclude with some speculations about the future uses of Artificial Intelligence in technique analysis.